The Art : new edition (Phaidon Press, 2012)
The Art book presents a whole new way of looking at art. Easy to use, informative and fun, it's an A-to-Z guide to the greatest painters, photographers and sculptors from medieval times to the present day. It debunks art-historical classifications by throwing together brilliant examples from all periods, schools, visions and techniques. The art book presents a fresh approach to art: an unparalleled visual sourcebook and a celebration of our rich and multi-faceted culture.